The Pure Intergenerational Problem and the UNESCO Decade of Education for Sustainable Development - Vladimirova, Katia (ETHICS IN PROGRESS, 2014)
This article aims to bring together some theory – research on climate  ethics, particularly the Pure Intergenerational Problem (PIP) introduced by Stephen Gardiner – and some practice – the new educational agenda proposed by the United Nations in 2002 and framed as the Decade of Education for Sustainable Development (DESD). PIP can be resolved (or rather, avoided) if a shift in values happens that would change the very context of the problem. On the other hand, DESD is aimed at promoting the values “inherent in sustainable development” and at enabling societal transformation and behavioral change. The main focus within the value shift in this article is on a particular set of values (principles, concerns) that relate present people to future generations in terms of moral responsibility. It is argued that the promotion of ethical considerations that are concerned with the distant future, and the future of humankind in general, can be a solution to the Pure Intergenerational Problem. The article also explores whether parts of this solution can already be found within the educational agenda of DESD.